2012
DOI: 10.1111/j.1748-1090.2012.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Using environmental enrichment to reduce the expression of abnormal behaviours in Greater rhea Rhea americana at Belo Horizonte Zoo

Abstract: Animals kept by zoos may express abnormal behaviours that are indicators of poor welfare. Environmental enrichment is a technique of providing items to animals that stimulate the expression of normal behaviours. The aim of this study was to evaluate the effects of providing simple environmental enrichment in the reduction of the expression of abnormal behaviour in captive‐born Greater rhea Rhea americana at Belo Horizonte Zoo, south‐eastern Brazil. As enrichment, fruit and vegetables were scatter fed to a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Male greater rheas walked, walked alert, stood alert, and foraged more after the provision of environmental enrichment and decreased the exhibition of abnormal behaviours; the same result has been observed in other studies with ratites and other birds (Meehan et al, 2003(Meehan et al, , 2004Christensen & Nielsen, 2004;Dias et al, 2011;Azevedo et al, 2013a). In all of these studies, environmental enrichment was used to stimulate foraging in animals.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Male greater rheas walked, walked alert, stood alert, and foraged more after the provision of environmental enrichment and decreased the exhibition of abnormal behaviours; the same result has been observed in other studies with ratites and other birds (Meehan et al, 2003(Meehan et al, , 2004Christensen & Nielsen, 2004;Dias et al, 2011;Azevedo et al, 2013a). In all of these studies, environmental enrichment was used to stimulate foraging in animals.…”
Section: Discussionsupporting
confidence: 70%
“…During enrichment use (enrichment phase), the same quantities of the normal diet continued to be offered to the birds in the feeder. Enrichment items were chosen based on Azevedo et al (2013a), which showed that new palatable food items are rewarding for greater rheas. The study was divided into three phases of 30 h: baseline (birds with no enrichment), enrichment (when the enrichment items were available to the birds) and post-enrichment (birds with no enrichment, when conditions returned to those of the baseline) (Young, 2003).…”
Section: Environmental Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, for example, the lack of natural pastures in the pen with bare ground of IRS could be perceived by Greater Rhea females as a stressful condition that affected their natural foraging behavior. It has been shown that environmental enrichment (fruits and vegetables scattered around the enclosure) reduced the abnormal behaviors in captive Greater Rheas and increased their time allocated to foraging and walking (Azevedo et al, ). The Greater Rhea is a highly selective feeder both in captivity (Bazzano et al, ) and in the wild (Martella et al, ); therefore, a rearing system that facilitates the development of the normal foraging behavior in females might reduce stress and optimize their welfare.…”
Section: Discussionmentioning
confidence: 99%
“…However, infected mice showed only a slight increase in activity, and this could be a direct reflection of infection with T. cruzi, as this parasite increases lethargy in animals 43 . Environmental enrichment techniques are known to diminish the expression of abnormal behaviors in many animal species 8,38,[44][45][46][47] . In the present study, abnormal behaviors did not decrease significantly during enrichment treatment in infected groups, showing that the items used may not be adequate for this.…”
Section: Il-10 (Pg/ml)mentioning
confidence: 99%